FORMULATION FORMULATION OF STRATEGY FOR SMALL CHOCOLATE PROCESSING INDUSTRY BASED ON SWOT ANALYSIS : CASE STUDY CV. PUTRA MATARAM - St HiJrah Alfiana; Rindam Latief; S Salengke (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
West Sulawesi Province ranks fourth in cocoa production in Indonesia in 2020 with a total production of 71,543 tons. . The use of domestic cocoa beans as raw material for domestic industries is still very low since most of the beans is exported in the fram of dry beans. Indonesia government has established cocoa processing industry as one of the sectors that is prioritized for development. CV. Putra Mataram is a small chocolate processing industry located in Polewali Mandar Regency which can be developed into a medium scale cocoa processing industry considering the availability of raw material. The purpose of this study was to identify and analyze the internal and external factors affecting the development of small scale chocolate industry and to determine the appropriat development strategy for CV. Putra Mataram. Qualitative data analysis was carried out by identifying the internal and external factors affecting the chocolate industry based on the results of the interview. The information obtained was reformulated and entered into the SWOT matrix. From the results of the SWOT analysis, there are 9 alternative development strategies that can be applied by CV. Putra Mataram. These strategies might also relevant to other small scale chocolate processing industries.